2002
DOI: 10.1046/j.1440-1746.2002.02649.x
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous primary adenocarcinoma, mucosa‐associated lymphoid tissue lymphoma and a stromal tumor in a Helicobacter pylori‐infected stomach

Abstract: We report the case of a 78-year-old man with Helicobacter pylori infection and three primary neoplasms of the stomach: adenocarcinoma, mucosa-associated lymphoid tissue (MALT) lymphoma and a gastrointestinal stromal cell tumor. Helicobacter pylori infection is associated with gastric carcinoma and MALT lymphoma, although their simultaneous occurrence is rare. Gastrointestinal stromal cell tumors have not been associated with infection to date. This appears to be the first report of the synchronous occurrence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 11 publications
0
37
0
6
Order By: Relevance
“…Kaffles et al 1 apresentam um doente em que foram diagnosticados, sincronicamente, adenocarcinoma, tumor estromal e linfoma.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Kaffles et al 1 apresentam um doente em que foram diagnosticados, sincronicamente, adenocarcinoma, tumor estromal e linfoma.…”
Section: Discussionunclassified
“…A ocorrência de tumores primários múltiplos no estômago não é rara, a incidência varia entre 2 a 3%, sendo a maioria dos casos composta por adenocarcinomas múltiplos ou associação entre adenocarcinoma e linfoma (MALT) 1 . Entretanto, adenocarcinoma e tumor mesenquimal (GIST) sincrônicos é muito raro, com apenas alguns relatos de casos na literatura 2 .…”
Section: Introductionunclassified
“…In one study, significantly more synchronous or metachronous gastrointestinal neoplasms were found in GIST patients compared to malignancies occur ring in the nor mal Hung arian population [11] . Furthermore, cases of synchronously occurring GIST and mucosa associated lymphoid tissue as well as GIST and carcinoid tumors of the stomach have been described in the literature [12,13] . Janovisk et al [14] recently reported a case of coexistence of hepatocellular carcinoma and GIST.…”
Section: Discussionmentioning
confidence: 99%
“…denaturing high-performance liquid chromatography (DHPLC) as described elsewhere (18). For each abnormal elution profile, genomic DNA was directly sequenced in both directions using a CEQ Dye-Terminator Cycle Sequencing kit (Beckman Coulter Inc., Miami, FL, USA) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…The association of gastric GIST and adenocarcinoma or mucosa-associated lymphoid tissue (MALT) lymphoma may be due to environmental or iatrogenic factors including Helicobacter pylori infection (18), dietary carcinogenesis and some drugs (19) that interact with the epithelial and stromal tissues in the stomach inducing the development of different neoplasms, and in addition, may be favored by a high incidence of tumors among the given population (20). Furthermore, it is possible that such an association may be caused by a single genetic aberration predisposing to the development of various histologic types of gastric neoplasms.…”
mentioning
confidence: 99%